2018
DOI: 10.2478/avutgs-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Growth of Green Algae Haematococcus Pluvialis Under Different Environmental Conditions

Abstract: Haematococcus pluvialis is a genus of green algae that keeps the high interest of the scientists for decades due to its capacity to synthesize astaxanthin. Among many others, astaxanthin is one of the most demanded natural anti-oxidant and the product of the future. It has the widest usage as source of nutrient rich food and health promoting compounds. Astaxanthin has got various applications in the nutraceuticals as immune system enhancer and anti-cancer agent, in the cosmetics as anti-aging component, as add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The slowest growth was observed in BG-11, which had the highest exponential phase compared to other culture media, reaching the stationary phase after 14 days of cultivation (Figure 1). Minasyan (2018) also observed that cultivation of H. pluvialis in the BG-11 medium achieved greater density with a more gradual growth rate. Nahidian, Ghanati, Shahbazi, and Soltani (2018), evaluating the development of the four cellular stages of H. pluvialis during 35 days of cultivation, also observed a longer growth time in a BG-11 than BBM medium.…”
Section: Growth Parametersmentioning
confidence: 67%
“…The slowest growth was observed in BG-11, which had the highest exponential phase compared to other culture media, reaching the stationary phase after 14 days of cultivation (Figure 1). Minasyan (2018) also observed that cultivation of H. pluvialis in the BG-11 medium achieved greater density with a more gradual growth rate. Nahidian, Ghanati, Shahbazi, and Soltani (2018), evaluating the development of the four cellular stages of H. pluvialis during 35 days of cultivation, also observed a longer growth time in a BG-11 than BBM medium.…”
Section: Growth Parametersmentioning
confidence: 67%